Development of IgE-mediated food allergies in children with history of food protein-induced allergic proctocolitis: a series of five cases - Tran, Kim L.; Wisner, Elizabeth L.; Jeha, George M.; Wall, Luke A. (Frontiers in Allergy, 2024)
Food protein-induced allergic proctocolitis (FPIAP) is a non-IgE-mediated allergic condition that presents with hematochezia in otherwise healthy infants. It is most commonly induced by cow’s milk protein via breast milk or formula. The prognosis for FPIAP is generally considered favorable with most infants achieving symptomatic resolution after diet modification. Most infants go on to tolerate the offending foods by 1-3 years of age. Over eight years at our institution, five patients were identified and noted to have FPIAP to cow’s milk during infancy with subsequent development of IgE-mediated allergic reaction to cow’s milk and other foods. All five cases developed other atopic disorders (atopic dermatitis in four cases). IgE-mediated cow’s milk allergy has persisted beyond the preschool years in at least two patients (currently 8 and 16 years old). For three of the patients, the IgE-mediated reaction to cow’s milk was severe with development of anaphylaxis or angioedema. In addition, three patients experienced anaphylaxis or angioedema to allergens other than milk. While FPIAP is a non-IgE mediated process traditionally thought not to progress past the first year of life, some infants with FPIAP develop severe, persistent IgE-mediated cow’s milk allergy. To our knowledge, this is the first detailed clinical description of such patients.